Real-world evidence for regulatory decision-making: updated guidance from around the world - Leah Burns; Nadege Le Roux; Robert Kalesnik-Orszulak; Jennifer Christian; Jennifer Dudinak; Frank Rockhold; Sean Khozin; John O’Donnell (Frontiers in Medicine, 2023)
Leveraging the value of real-world evidence (RWE) to make informed regulatory decisions in the field of health care continues to gain momentum. Improving clinical evidence generation by evaluating the outcomes and patient experiences at the point-of-care would help achieve the ultimate aim of ensuring that effective and safe treatments are rapidly approved for patient use. In our previous publication, we assessed the global regulatory landscape with respect to RWE and provided a review of the regional availability of frameworks and guidance through May 2021 on the basis of 3 key regulatory elements: regulatory RWE frameworks, data quality guidance, and study methods guidance. In the current review, we have updated and elaborated upon recent developments in the regulatory RWE environment from a regional perspective under the same 3 regulatory elements stated above. In addition, we have also included a new category on procedural guidance. The review also discusses the perceived gaps and potential opportunities for future development and harmonization in this field to support framework establishment in regions without pre-existing RWE policies. Additionally, the article reviews current developments of health technology assessment (HTA) bodies pertaining to RWE and discusses the status of evidentiary alignment among regulators and HTA agencies.